Ontology-Based Matchmaking and Scheduling for Manufacturing as a Service - Duran-San Martin, C (Elsevier B.V., 2025)
The pressure to develop a resilient value chain is currently a significant challenge due to a wide range of influences and disruptive factors. In achieving resilience, Manufacturing as a Service (MaaS) is a new approach with the potential to increase the responsiveness, flexibility, and scalability of manufacturing industries. The manufacturing services offered must match the specific requirements of the companies requesting them. Based on the analysis of the current state of knowledge, a three-stage ontology-based matchmaking approach is proposed to support human decision-makers in satisfying on-demand needs through the use of shared manufacturing resources offered as services. The capability of the proposed approach to semantically connect MaaS users is demonstrated for a MaaS scheduling service, which coordinates the execution of a set of on-demand manufacturing jobs by shared resources. Despite the constraints associated with the technical and organizational dimensions of industrial sectors, as well as with the complexity of supply chain dynamics, several key levers for expanding the adoption of MaaS are discussed throughout this paper. © 2025 Elsevier B.V.. All rights reserved.